MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN WINDOWS SHOPPING - Nurhabibah, Nanun (MGMP PAI Jawa Barat, 2023)
This research aims to improve student learning outcomes in the material Achieving Success with Optimism, Endeavor and Tawakal through the application of the Windows Shopping learning model in Class IX F of SMP Negeri 1 Jalancagak. The PTK model used in this research is the Stephen Kemmis and Robin Mc model. Taggart. This research uses classroom action research procedures with two cycles, namely cycle I and cycle II. In each cycle, the 2 initial meetings are learning and the last 1 meeting is an evaluation test with a target class average score or minimum completeness, namely 75. The subjects of this research were students in class IX F of SMP Negeri 1 Jalancagak, totaling 32 students. The average post test class score in cycle I was 72.97 with 18 students who completed the KKM (56.25%) and the average post test score in cycle II was 86.25 with 29 students who completed the KKM (90.63 %). The results of this study showed an increase in the average value of 13.28 (18.20%). Based on the research results, it can be concluded that learning through the application of the Windows Shopping learning model can improve student learning outcomes in the material Achieving Success with Optimism, Endeavor and Tawakal in class IX F of SMP Negeri 1 Jalancagak. Keywords: learning outcomes, achieving success with optimism, endeavor and trust, windows shopping and pai.bp